Pengaruh Dukungan Organisasi dan Budaya Organisasi terhadap Disiplin Kerja Perawat di RS. Dedy Jaya Brebes - Robert Robert; Dasrun Hidayat; Budi Santoso (Lembaga Pengembangan Kinerja Dosen, 2026)
Nurse discipline is a crucial factor in achieving hospital objectives in delivering high-quality healthcare services. However, issues related to work discipline are still frequently found in various healthcare facilities, including RS Dedy Jaya Brebes. Prominent problems include a high number of written warnings, low achievement of response time quality indicators, and a high rate of tardiness in work attendance. This study aims to analyze the effect of organizational support and organizational culture on nurses’ work discipline at RS Dedy Jaya Brebes. This research employed a quantitative method with an explanatory approach. The study population consisted of all active nurses at RS Dedy Jaya Brebes, with a total sampling technique involving 62 respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that organizational support has a positive and significant effect on nurses’ work discipline when tested partially. Likewise, organizational culture also has a positive and significant effect on nurses’ work discipline. Simultaneously, organizational support and organizational culture jointly have a positive and significant effect on nurses’ work discipline. These findings imply that improving nurses’ work discipline can be achieved through strengthening organizational support and fostering a conducive organizational culture.